Optimization of double boiling condition for kelulut honey processing using response surface methodology - A. Rahman, Atikah; M. Fauzi, Akhmazillah; Razali, Faiz (The Italian Association of Chemical Engineering (AIDIC), 2018)
This study was conducted to investigate the combined effects of temperature and time of double boiling treatment on the quality of Kelulut honey using Response Surface Methodology (RSM). Three-level factorial design employed nine runs with duplicates under different combination of temperature (30 – 60 °C) and time (10 – 60 min) was developed. Quality of Kelulut honey in this experiment was analyzed under six parameters which are physicochemical properties (pH, moisture content, total solids, and total soluble solids), and nutritional properties (brown pigment and antioxidant activity). Statistical analysis revealed that treatment variables give coefficient of determination, R2 in the range of 46.21 % to 83.16 % that indicates an adequate to strong correlation between the experimental and predicted response values. As treatment temperatureincreases, total solids and total soluble solids increase while moisture content decreases. In addition, treatment conditions give significant effect on brown pigment along with highest R2 value (83.17 %). Theoptimal setting of the experimental factors has been determined by desirability approach at temperature of 60 °C with treatment time of 35 minutes. This study is currently a novel report on optimization of combined temperature and time of double boiling treatment which provides a new insight on Kelulut honey processing.